2004
DOI: 10.1097/00042728-200405000-00031
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Face-Lift for Correction of Middle Face Aging Utilizing a Minimally Invasive Technique

Abstract: OBJECTIVE. A minimally invasive face-lifting approach aimed at rejuvenation of the midface was examined, for patients with concerns limited to midfacial aging.METHODS. An incision in the preauricular area and then minor undermining to lift superfical musculo apponeurotic system (SMAS), followed by SMAS plication and removal of skin laxity in the midface, results in excellent superolateral reversal of inferomedial displacement of the aging vector. RESULTS AND CONCLUSION. A minimally invasive procedure was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It has been found that midface elevation can be achieved using two or three separate non‐absorbable Mersilene suspension sutures, 14 but this can be achieved using a single Monograms. The anchors of this specialized suture catch the deeper planes of the subcutaneous tissues in an imbricating fashion, thereby effacing the overlying nasolabial fold and elevating the malar fat pad.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that midface elevation can be achieved using two or three separate non‐absorbable Mersilene suspension sutures, 14 but this can be achieved using a single Monograms. The anchors of this specialized suture catch the deeper planes of the subcutaneous tissues in an imbricating fashion, thereby effacing the overlying nasolabial fold and elevating the malar fat pad.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these procedures have significant risk, along with downtime from 2 to 6 weeks. More recently, the S‐lift and its variations have been developed in an attempt to minimize risk and downtime 20,21 . However, it still involves surgery and downtime.…”
Section: Discussionmentioning
confidence: 99%
“…I would like to comment on the article “Anterior Face‐Lift for Correction of Middle Face Aging Utilizing a Minimally Invasive Technique,” by Bisaccia and colleagues 1 …”
mentioning
confidence: 95%